2021
DOI: 10.3348/kjr.2020.0836
|View full text |Cite
|
Sign up to set email alerts
|

Why Is a b-value Range of 1500–2000 s/mm2 Optimal for Evaluating Prostatic Index Lesions on Synthetic Diffusion-Weighted Imaging?

Abstract: Objective It is uncertain why a b-value range of 1500–2000 s/mm 2 is optimal. This study was aimed at qualitatively and quantitatively analyzing the optimal b-value range of synthetic diffusion-weighted imaging (sDWI) for evaluating prostatic index lesions. Materials and Methods This retrospective study included 92 patients who underwent DWI and targeted biopsy for magnetic resonance imaging (MRI)-suggested index lesions. We generated sDWI at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…34 Finally, quantitative diffusion MRI enables "computed" diffusion MRI, that is, synthesizing arbitrary high b-values beyond those acquired, with several promising applications. [35][36][37]…”
Section: Potential For Improved Value Through Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Finally, quantitative diffusion MRI enables "computed" diffusion MRI, that is, synthesizing arbitrary high b-values beyond those acquired, with several promising applications. [35][36][37]…”
Section: Potential For Improved Value Through Quantificationmentioning
confidence: 99%
“…Indeed, by removing intra‐ and inter‐reader variability in image interpretation, quantitative diffusion MRI (similarly to other quantitative imaging methods) may provide added value in basic and clinical research (e.g., clinical trials with improved power due to reduced measurement variability), 33 as well as clinical care 34 . Finally, quantitative diffusion MRI enables “computed” diffusion MRI, that is, synthesizing arbitrary high b ‐values beyond those acquired, with several promising applications 35–37 …”
Section: Quantitative Diffusion Mrimentioning
confidence: 99%
“…Theoretically, when signal attenuation arrives into ultra-high b-value region, the sensitivity to smaller spatial scale enhances and enables DWI to explore tissue microstructure on complexity and heterogeneity more powerfully than routine DWI [ 23 ]. In fact, previous studies has showed that UHBV-DWI performed better than traditional DWI in tumor grading [ 16 ] and detection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ultra-high b-value DWI (UHBV-DWI) is increasingly explored in relation to the cerebral system [ 15 17 ] and prostate cancer [ 18 , 19 ] and has showed considerable potential in tumor grading and detection. In contrast, there is lack of research with respect to the investigation of UHBV-DWI in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the DCE parameters used varied: the phase number range was 2–90 and the phase duration range was 3–60 seconds. The highest b-values of 800–2000 sec/mm 2 were not consistent with the highest b-values of ≥ 1400 sec/mm 2 [ 1 19 ]. There are several possible explanations for these findings.…”
Section: Discussionmentioning
confidence: 99%